Probiotic additive affects muscle growth of Nile tilapia (Oreochromis niloticus) - Silva, Vinícius Vasconcelos; Salomão, Rondinelle Artur Simões; Mareco, Edson Assunção; Dal Pai, Maeli [UNESP]; Santos, Vander Bruno (Hindawi, 2021)
This study aimed to evaluate the probiotic additive on tilapia growth by establishing growth curves, as well as assessing the morphology of the muscular and ventral subcutaneous adipose tissues, carcass characteristics and gene expression that controls growth. Fingerlings of 5 g were grown in a recirculating aquaculture system consisting of 15 water tanks (0.25 m3) at 80 fish/m3. Fish were fed three times daily with the same feed, using additive with Bacillus subtilis, Bifidobacterium bifidum, Enterococcus faecium, Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus lactis, Lactobacillus plantarum and Pediococcus acidilactici (1.0 × 109 CFU/g). They were assessed levels of 0.1% and 0.2% of additive probiotic homogenized in 2% soy oil and sprinkled over the feed. Exponential models were fit to compare growth rates, weighing samples at days 0, 30, 60 and 90 of cultivation. The probiotic mixture used in this study as feed additive may be diffused in aquaculture in order to increase productivity, as demonstrated by feed conversion rate, final weight and growth (13%–37% for 0.1% and 0.2% of additive level respectively). Growth stimulation occurred by white muscle fibre hypertrophy, accompanied by inhibition of MyoD and myostatin, gene expression and increase in the number of intestinal villi, ensuring greater absorption and utilization of nutrients provided in the diet.
Keywords: fibre hypertrophy; growth rate; intestinal villi; Lactobacillus; myostatin